2022
DOI: 10.1101/2022.11.04.515174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bold but not innovative in an urban exploiter, the red fox (Vulpes vulpes)

Abstract: Urbanisation is the fastest form of landscape transformation on the planet, but our understanding of how wildlife responds to such changes is still in its infancy. Red foxes (Vulpes vulpes) are renowned for thriving in urban settings where they have many opportunities to exploit food within or in close proximity to a wide variety of human-made objects (e.g., litter and contents of outdoor bins). The visibility of such behaviour has likely contributed to urban foxes being labelled as bolder, cunning, and a gene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…West, Wales, West Midlands, Yorkshire and the Humber), and gender as random factors, as a prior study suggested that fox-related attitudes and beliefs may be different in different regions of the UK (Morton et al, 2023) and because previous studies have found gender sampling effects on fox-related attitudes (Kimmig et al, 2020). Although age and degree of urbanisation can also impact fox-related attitudes (Kimmig et al, 2020), there were no significant differences in participants' mean age (F(3, 1369) = .964, P = .409) and degree of urbanisation (F(3, 1369) = .895, P = .443) across our treatments, hence, we opted against including these variables within our models to avoid overparameterization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…West, Wales, West Midlands, Yorkshire and the Humber), and gender as random factors, as a prior study suggested that fox-related attitudes and beliefs may be different in different regions of the UK (Morton et al, 2023) and because previous studies have found gender sampling effects on fox-related attitudes (Kimmig et al, 2020). Although age and degree of urbanisation can also impact fox-related attitudes (Kimmig et al, 2020), there were no significant differences in participants' mean age (F(3, 1369) = .964, P = .409) and degree of urbanisation (F(3, 1369) = .895, P = .443) across our treatments, hence, we opted against including these variables within our models to avoid overparameterization.…”
Section: Discussionmentioning
confidence: 99%
“…Negative attitudes and beliefs towards the conservation of predators can be influenced by a variety of factors, including over-generalization of the risks they pose towards people (Ashish et al, 2022). In the case of foxes, there is a growing potential for human-wildlife conflict if, for example, foxes are becoming bolder within urban spaces (Morton et al, 2023), and people perceive the risks resulting from such behaviour as being higher (Brand & Baldwin, 2020;Soulsbury & White, 2015). Studies suggest that while urban foxes may behave more boldly than rural populations (Morton et al, 2023), people's attitudes and beliefs about foxes may also be influenced by popular culture, whichas with other carnivore speciescan be highly sensationalised and negative (Bridge & Harris, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations